2013
DOI: 10.1089/ars.2012.4653
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Peptide from Transforming Growth Factor-β1Type III Receptor Inhibits NADPH Oxidase and Prevents Oxidative Stress in the Kidney of Spontaneously Hypertensive Rats

Abstract: We demonstrate that P144 inhibits NADPH oxidases and prevents oxidative stress in kidneys from hypertensive rats. Our data also suggest that these effects are associated with the renal antifibrotic effect of P144.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
4
17
0
Order By: Relevance
“…EGFR-via transactivation-has the potential to mediate signaling of non-EGFR ligands and thereby serve as a heterologous transducer of cellular signaling. EGFR transactivation in cardiac cells has been observed following stimulation with several vasoactive substances and well-known inducers of cardiomyocyte hypertrophy such as AngII, phenylephrine, endothelin-1 and aldosterone [32][33][34][35]. In CFs, β-adrenergic receptor-dependent changes in cytokine expression are also predominantly mediated through an EGFR-sensitive manner [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR-via transactivation-has the potential to mediate signaling of non-EGFR ligands and thereby serve as a heterologous transducer of cellular signaling. EGFR transactivation in cardiac cells has been observed following stimulation with several vasoactive substances and well-known inducers of cardiomyocyte hypertrophy such as AngII, phenylephrine, endothelin-1 and aldosterone [32][33][34][35]. In CFs, β-adrenergic receptor-dependent changes in cytokine expression are also predominantly mediated through an EGFR-sensitive manner [36].…”
Section: Discussionmentioning
confidence: 99%
“…HB-EGF is known to induce cell activation in various cell types, including cardiac cells via transactivation of EGFR. In CFs and cardiomyocytes, it has been demonstrated that cellular signaling induced by inflammatory agonists and proteases, closely related to cardiac remodeling, is dependent upon HB-EGF shedding and subsequent EGFR activation [33,38,39]. Therefore, further approaches, such as knockdown EGFR or HB-EGF expression, might be considered to be future strategies for validating the results obtained with pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis and CKD patients manifest impaired mitochondrial respiration indicative of dysregulated aerobic metabolism and increased oxidative stress . NADPH oxidases (NOX) family has been significantly induced during renal injury, and reduced NOX activity is associated with renal protection in pre‐clinical models of CKD . Nox1, Nox2, and Nox4, which are expressed in both human and rodent kidneys, have a central role in mediating oxidative stress in CKD .…”
Section: Discussionmentioning
confidence: 99%
“…29 NADPH oxidases (NOX) family has been significantly induced during renal injury, and reduced NOX activity is associated with renal protection in pre-clinical models of CKD. 30,31 Nox1, Nox2, and Nox4, which are expressed in both human and rodent kidneys, have a central role in mediating oxidative stress in CKD. 32 These studies suggest that oxidative stress, involving various reactive oxygen and nitrogen species, exerts a promoted role in the progress of CKD development.…”
Section: Fgf1 Treatment Suppressed Diabetes-induced Er Stress and Umentioning
confidence: 99%
“…53,54 These peptides have shown an antagonist effect over TGFb-dependent processes in cellular cultures and a strong TGF-b inhibitory effect in different animal models. 23,[55][56][57] PD Fluid Exposure Model in Mice Female C57BL/6 mice between 12 and 16 weeks of age were used in this study (Harlan Interfauna Iberica, Barcelona, Spain). The experimental protocol used was in accordance with the National Institutes of Health Guide for Care and Use of Laboratory Animals and approved by the Animal Ethics Committee of the Centro de Biología Molecular "Severo Ochoa."…”
Section: Reagentsmentioning
confidence: 99%